2017
DOI: 10.1016/j.drugalcdep.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal buprenorphine treatment and infant outcome

Abstract: Background and Objectives Maternal buprenorphine maintenance predisposes the infant to exhibit neonatal abstinence syndrome (NAS), but there is insufficient published information regarding the nature of NAS and factors that contribute to its severity in buprenorphine-exposed infants. Methods The present study evaluated forty-one infants of buprenorphine-maintained women in comprehensive substance use disorder treatment who participated in an open-label study examining the effects of maternal buprenorphine ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 27 publications
(33 reference statements)
0
13
0
1
Order By: Relevance
“…The third paper [ 48 ] found no correlation between nicotine or its metabolites in the meconium and NAS expression or neonatal outcomes (statistical analysis not provided). The fourth paper [ 49 ] concluded that maternal cigarette exposure had no impact on neonatal outcomes, including NAS severity ( p = 0.36). Note, all four papers that examined only buprenorphine had small sample sizes ( n = 10 [ 48 ]; n = 15 [ 47 ]; n = 23 [ 46 ]; and n = 41 [ 49 ]), which made it much less likely that a statistical difference attributable to tobacco consumption could be detected.…”
Section: Resultsmentioning
confidence: 99%
“…The third paper [ 48 ] found no correlation between nicotine or its metabolites in the meconium and NAS expression or neonatal outcomes (statistical analysis not provided). The fourth paper [ 49 ] concluded that maternal cigarette exposure had no impact on neonatal outcomes, including NAS severity ( p = 0.36). Note, all four papers that examined only buprenorphine had small sample sizes ( n = 10 [ 48 ]; n = 15 [ 47 ]; n = 23 [ 46 ]; and n = 41 [ 49 ]), which made it much less likely that a statistical difference attributable to tobacco consumption could be detected.…”
Section: Resultsmentioning
confidence: 99%
“…Reports of lower birth weight associated with higher dose of methadone or buprenorphine at delivery in opioid maintained pregnant women could support this. 29,168,169 There is also evidence from animal research to support a causal effect of opioids on fetal growth. 170 However, there are myriads of associated risk factors, like poor maternal nutrition, maternal infections, and co-exposure to non-opioid drugs, and it is still unclear if opioids have a direct, causal effect on human fetal growth.…”
Section: Socio Economic Disparitiesmentioning
confidence: 99%
“…24,25 Undoubtedly, the relationship between opioid exposure, neural circuitry changes and psychosocial factors are complex. [26][27][28][29] Indeed, pre-and postnatal environmental factors and stressors are important variables in the maturation of brain circuitry. 26,27,[30][31][32] Nontheless, the principal mechanisms of neural injury induced by opioids early in development remain a gap in knowledge.…”
Section: Introductionmentioning
confidence: 99%